To find the x and the y intercepts it is necessary to replace for 0 the variable that you don't need and then clear the needed one from the equation.
It means, to find the x intercept, replace y for 0 and clear x from the equation:
![\begin{gathered} 2x-3y=-18 \\ 2x-3\cdot0=-18 \\ 2x=-18 \\ x=-(18)/(2) \\ x=-9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/rnjl3cgz1p16mtzy7wattev4xfdxe4amaq.png)
The x intercept is -9
To find the y intercept, replace x for 0 and clear y from the equation:
![\begin{gathered} 2x-3y=-18 \\ 2\cdot0-3y=-18 \\ -3y=-18 \\ y=-(18)/(-3) \\ y=6 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/309tsmk0okekjsipdk0s70uxsigvogwf40.png)
The y intercept is 6